Spiritual Seeking dan Flourishing Mahasiswa Seminari di Indonesia: Kontribusi dari Managing Identity - Aditya, Yonathan; Martoyo, Ihan (Veritas : Jurnal Teologi dan Pelayanan, 2024)
Spiritual education and growth often involves a searching and struggling phase that can be disruptive to one’s well-being. However, if these questing phases are indeed a natural part of the spiritual journey, then strategies are needed to manage them. This article examines the relationship between the psychological phase of seeking (Quest) and well-being (Flourishing), as well as the contribution of the Managing Identity dimension of the concept of Self-Differentiation. Data were collected from 303 seminary students from 28 theological colleges in Indonesia. Multilevel regression analysis found that Quest did negatively predict seminary students’ well-being (β=-.13, p<.01), however Managing Identity of Self-Differentiation contributed more positively to well-being (β=.61, p<.01). The implications of these findings will be discussed. The Quest and Self-Differentiation dimensions were found to be closely related to Reformed theology, soteriology and ecclesiology, and the focus on the reality of the Trinity that models Christian life.